Reinforcement’s incidental effects on reproductive isolation between conspecifics - Comeault, Aaron A.; Matute, Daniel R. (Current zoology, 2016)
Abstract Reinforcement—the process whereby maladaptive hybridization leads to the strengthening of prezygotic isolation between species—has a long history in the study of speciation. Because reinforcement affects traits involved in mate choice and fertility, it can have indirect effects on reproductive isolation between populations within species. Here we review examples of these “cascading effects of reinforcement” (CER) and discuss different mechanisms through which they can arise. We discuss three factors that are predicted to influence the potential occurrence of CER: rates of gene flow among populations, the strength of selection acting on the traits involved in reinforcement, and the genetic basis of those traits. We suggest that CER is likely if (1) the rate of gene flow between conspecific populations is low; (2) divergent selection acts on phenotypes involved in reinforcement between sympatric and allopatric populations; and (3) the genetic response to reinforcement differs among conspecific populations subject to parallel reinforcing selection. Future work continuing to address gene flow, selection, and the genetic basis of the traits involved in the reinforcement will help develop a better understanding of reinforcement as a process driving the production of species diversity, both directly and incidentally.